Association between inflammatory biomarker profiles and cardiovascular risk in individuals with and without HIV. (15th March 2023) - Sukumaran, Luxsena; Kunisaki, Ken M.; Bakewell, Nicholas; Winston, Alan; Mallon, Patrick W.G.; Doyle, Nicki; Anderson, Jane; Boffito, Marta; Haddow, Lewis; Post, Frank A.; Vera, Jaime H.; Sachikonye, Memory; et al.
Abstract : Background: People with HIV have an increased risk for cardiovascular morbidity and mortality. Inflammation and immune activation may contribute to this excess risk. Methods: We assessed thirty-one biomarkers in a subset of POPPY participants and identified three distinct inflammatory profiles: 'gut/immune activation', 'neurovascular', and 'reference' (relatively low levels of inflammation). Ten-year cardiovascular disease (CVD) risk predictions were calculated using the QRISK, Framingham Risk Score (FRS) and the Data Collection on Adverse effects of anti-HIV Drugs (D:A:D) algorithms. The distributions of CVD risk scores across the different inflammatory profiles, stratified by HIV status, were compared using median quantile regression. Results: Of the 312 participants included [70% living with HIV, median (interquartile range; IQR) age 55 (51–60) years; 82% male; 91% white], 36, 130, and 146 were in the 'gut/immune activation', 'neurovascular', and 'reference' cluster, respectively. The median (IQR) QRISK scores were 9.3% (4.5–14.5) and 10.2% (5.5–16.9) for people with and without HV, respectively, with similar scores obtained with the FRS and D:A:D. We observed statistically significant differences between the distributions of scores in the three clusters among people with HV. In particular, median QRISK [5.8% (1.0–10.7) and 3.1% (0.3–5.8)] scores were higher, respectively, for those in the 'gut/immune activation' and 'neurovascular' clusters compared to those in the reference cluster. Conclusions: People with HIV with increased gut/immune activation have a higher CVD risk compared to those with relatively low inflammation. Our findings highlight that clinically important inflammatory subgroups could be useful to differentiate risk and maximise prediction of CVD among people with HIV.